Evaluation of technological and functional properties of breakfast cereal based on flaxseed oil cake and broken rice flour - Alireza Abbasi; Arash Koocheki; Elnaz Milani; Mohebbat Mohebbi (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2022)
[1]Introduction: Breakfast cereal products are considered as an important meal for athletes and children. By changing eating habits and increasing the consumption of these products, choosing healthy and nutritious raw materials such as whole grains to produce breakfast cereals with great impact on people's health. Rice grain as a technologically important source of starch causes the expansion of extruded products. Since in the production of breakfast cereal and baby food products, exclusively starch with low amylose is used, this indicates the suitability of this source for productionof such products. During the dehusking process, about 14% of the rice is broken to smaller grains, which is commercially classified as a low-value product. The broken rice can be converted to rice flour and used as a raw material in various types of food products. To maintain consumer demand for healthy diets, it is necessary to use high-fiber flours because these types of products will be able to modify the process of decomposition of starch. Although the integration of fiber in products has technological challenges, but by using rice grain as an important source of starch, the technological properties, expansion index, volumetric density and texture (texture hardness and brittleness) can be accepted. At present, modified starch derivatives are widely used in the food industry due to the increase in the quality of the final product. In the production of ready-to-use products for flaking, puffing, a process called extrusion is used. In this process, the product suddenly loses its moisture and leads to the creation of a dense structure containing pores. In this study, the effect of extrusion cooking process parameters on the desired characteristics of flax and rice meal breakfast cereal product with desirable physicochemical and sensory properties was investigated. Materials and Methods: Extrusion: In this study, a parallel twin-screw extruder (Jinan Saxin, China) was applied, die diameter of 3 mm, and extrusion temperature of 140 ℃. Central composite statistical design was used to study the effect of feed moisture (12, 15 and 18%), screw speed (140, 170 and 200 rpm) and Flaxseed oil cake addition (10, 20 and 30%) on technological and functional properties expanded extrudates. The chemical composition of flax meal and rice flour was measured by standard AACC (2000) methods. The expansion ratio was calculated by dividing the mean diameter (mm) by the diameter of the extruder die (4 mm) (Brennan et al, 2008). Textural measurement: The hardness of the extruded breakfast cereals was measured using Texture Analyzer (TA plus Ametek, UK). The cylinder steel probe (2 mm diameter) was set to move at a speed of 1 mm/s The samples were punctured by the probe to a distance of 10 mm. Bowl life hardness: Breakfast cereal samples were immersed in whole milk (3% fat) at 5 ° C for 3 minutes, Then rinsing was performed for 10 seconds and finally the samples were tested similar to the tissue hardness test procedure before immersion by a tissue analyzer (Oliveira et al, 2017). The color parameters L* (lightness), a*(redness), b*(yellowness) values of the samples were determined by the Hunterlab machine (Reston VA, US) (Rhee et al, 2004). Water absorption index in terms of grams of bonded water was calculated. The WSI of the dry solids regained through the evaporation of the supernatant obtained from the water absorption test was calculated (Alam et al, 2019). Sensory evaluation was performed using a 9-point hedonic test. Response surface methodology was applied for experimental data using a commercial statistical package, Design Expert (version 7.0) for the generation of response surface plot and statistical analysis of the experimental data. Results and Discussion: One of the most important parameters in the evaluation of breakfast cereal products is the amount of bowl-life hardness, which in this study, the highest amount was obtained at the level of 30% of flaxseed meal, 18% moisture and the lowest amount of screw rotation speed. After immersing breakfast cereal in milk, by increasing the percentage of flax meal due to the harder flow path, moisture absorption decreases and thus prevents the expansion of the product and increases the density of the mass and the hardness of the tissue. Due to the formation of a layer of lipids and micelles on the surface of the product prevents moisture transfer and absorption, so tissue hardness decreases and bowl-life hardness time increases. In fact, the amount of moisture absorption is a good model that shows the potential of bowl hardness-life of the samples. It is also compact and dense, which increases the retention time of breakfast cereal texture. Moisture can also reduce the shear force as a plasticizer and increase the amount of moisture absorption of the product. While increasing the speed of screw rotation, the effect of shear force on starch dextrinization increases and reduces moisture absorption. Another important feature of breakfast cereals is the lightness index, the highest value of which was obtained at the speed of screw rotation, humidity and low flax meal level. In the study of sensory properties of products produced at meal levels less than 20%, moisture content less than 15% and screw speed of 200 rpm showed the highest overall acceptance.